The Beneficial Effects of Cognitive Training With Simple Calculation and Reading Aloud (SCRA) in the Elderly Postoperative Population: A Pilot Randomized Controlled Trial - Kulason, Kay; Nouchi, Rui; Hoshikawa, Yasushi; Noda, Masafumi; Okada, Yoshinori; Kawashima, Ryuta (Frontiers in Aging Neuroscience, 2018)
Background. There has been little research conducted regarding cognitive treatments for the elderly postsurgical population. Patients aged 60 and above have increased risk of postoperative cognitive decline, a condition in which cognitive functions, and consequently quality of life, are negatively affected after surgery. In order to maintain a high quality of life, elderly postsurgical population may benefit from treatment to maintain and/or improve their cognitive functions. This pilot study investigates the effect of simple calculation and reading aloud (SCRA) cognitive training in elderly Japanese postsurgical patients. Methods. Elderly patients undergoing non-cardiovascular thoracic surgery under general anesthesia were recruited (n=12). Subjects were randomly divided into two groups—one that receives 12 weeks of SCRA intervention, and a waitlisted control group. Before and after the intervention, we measured cognitive function (Mini-Mental Status Exam-Japanese (MMSE-J), Frontal Assessment Battery (FAB), computerized Cogstate Brief Battery (CBB)) and emotional state (General Health Questionnaire-12 (GHQ-12), Geriatric Depression Scale (GDS), Quality of Life Scale-5 (QOL-5)) Results. Group difference analyses using ANCOVA with permutation test showed that the intervention SCRA group had a significant improvement in FAB motor programming sub-score, GDS, and QOL-5 compared to the control group. Within group analyses using Wilcoxon signed-rank test to compare baseline and follow-up showed that the SCRA intervention group total FAB scores, FAB motor programming sub-scores, and QOL-5 scores were significantly improved. Discussion. This pilot study showed that there are important implications for the beneficial effects of SCRA intervention on cognitive function and emotional state in the postoperative elderly population; however, further investigations are necessary to reach any conclusions. Trial registration. This study was registered with the University Hospital Medical Information Network (UMIN) Clinical Trial Registry (UMIN000019832).